O perfil contencioso climático brasileiro sob o recorte temporal de 2019 a 2022: estudos e perspectivas - Lazzaretti, Luisa Lauermann (Universidade do Vale do Rio dos Sinos, 2022)
Brazilian climate litigation is still a recent movement, but with an increase in repercussion, especially after 2020, when there was a considerable growth in the number of this type of process brought to the judiciary. Considering the challenge of this phenomenon in the national context, the main goal is to analyze the profile of these new national climate litigations be, the repercussions and the challenges that these actions represent for Brazil? The hypothesis is that climate litigation will be a positive strategy for more effective Brazilian climate governance and will have a pedagogical character by simulating debate among the various national actors, manly from civil society, consisting of a strategic litigations movement. Furthermore, considering Brazilian law, it is believed that there will be some sensitive issues such as procedure law and complex scientific matters, with repercussions on the Separation of Powers, Civil Liability, tort law, among others. This work has the scope to analyze how this phenomenon is occurring in the Brazilian judiciary, specifically after the year 2019 in which the first climate actions themselves were filed. For this, the deductive method was used, starting from the study of the general theory of climate change and climate litigation to, finally, carry out the analysis of Brazilian climate cases brought to the judiciary after the year 2019. In addition, documentary and exploratory analysis was carried out in two important sites that catalog the climatic disputes of the Brazilian jurisdiction. For the analysis of climate disputes in Brazil, an empirical research procedure will be used through the case study. In short, national climate litigation has proved to be a space for discussion between different interested actors and with some advances such as the recognition of climate as an autonomous legal asset that needs jurisdictional protection. In addition, it was observed the formation of a Climate Change Law with doctrinal material and it is expected that the consolidation of specialized jurisprudence.
Keywords: Mudanças climáticas; Litigância climática; Judiciário brasileiro; Climate change; Climate litigation; Brazilian judiciary; ACCNPQ::Ciências Sociais Aplicadas::Direito